Human Resource Development Strategy to Support Sustainable Economic Growth - Pramanda, Ryan (Journal of Economic Growth and Development Review, 2024)
This research examines the strategic role of human resource (HR) development in supporting sustainable economic growth. Using a mixed methods approach, this study combines secondary data analysis from international organizations, comparative case studies from three countries with different levels of economic development, a Delphi survey with 20 experts, and in-depth interviews with 15 key stakeholders. The research results show a strong positive correlation between investment in human resource development and sustainable economic growth. The three main strategies identified are education system reform with a focus on 21st century skills, industry-based training through public-private partnerships, and flexible labor market policies. The impact of this strategy varies across economic sectors, with technology and renewable energy sectors showing the greatest benefits. The conceptual model developed emphasizes the importance of a holistic approach in human resource development. This study concludes that strategic investment in human resource development is the key to achieving sustainable and inclusive economic growth, especially in the face of rapid technological change. Policy implications and recommendations for future research are also discussed.